Pojok Baca sebagai Sarana Peningkatan Literasi Peserta Didik di Sekolah Dasar - Andini Zeptiani; Armedia Desita Lestari; Diah Mulfi Cahya Prameswari; Endrise Septina Rawanoko (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Education is an effort to help students develop and enhance their knowledge, skills, values, attitudes, and behaviors that are beneficial. The Ministry of Education and Culture initiated the literacy movement. However, Indonesia is one of the countries with the lowest literacy rates. The purpose of writing this article is to demonstrate that reading corners can help improve students' literacy skills. The goal of this article is to highlight reading corners as a means of enhancing students' literacy in elementary schools. The method used in this article is qualitative, with a literature study approach to gather data and information from books, journals, and other reference materials. Data collection techniques in this study included observation, interviews, and documentation. The subjects in this study were three class teachers and 30 students in total. Based on the findings of this study, the implementation of reading corners can increase students' motivation to develop their literacy skills. Furthermore, reading corners also involve student interactions with the books provided and discussions with peers.